Data mining trends and applications in criminal science and investigations - Isafiade, Omowunmi E. 1982-; Bagula, Antoine B. 1960- (Advances in data mining and database management (ADMDM) book series, 2016)
This book presents scientific concepts and frameworks of data mining and analytics implementation and uses across various domains, such as public safety, criminal investigations, intrusion detection, crime scene analysis, and suspect modeling